Voltage dip mitigation in distribution networks - Hareesh, Kumar (2019)
In this era of rapidly growing industries, power systems are facing many new challenges, especially the distribution side. Many semiconductor industries including wafer manufacturing are in need of high quality power and the fluctuation in voltage is a major concern for them. Voltage dip and voltage swell can lead to failure or malfunction of critical equipment leading to both operation and financial losses for the customers. Both voltage dip and voltage swell cannot be eliminated from the power system since system faults, weather and disturbances are stochastic in nature. However, they can be mitigated. Mitigation of voltage dip is possible by injecting either a shunt current or a series voltage. At present, integration of renewable energy sources in the grid is also a major concern because existing power system was not built to accommodate the renewable sources. By integrating, there is a large voltage dip or swell occurred. Our major concern in this project is the voltage dip. Different test cases for voltage dip condition such as large magnitude and short duration, large magnitude and long duration, small magnitude and short duration, and small magnitude and long duration will be studied. In this project, both balanced and unbalanced voltage dips caused by short circuit faults will be simulated for different operating conditions in a distribution network using MATLAB/Simulink and effective voltage dip mitigation method (mainly STATCOM) will be explored and implemented. Modeling of the STATCOM and its MATLAB results will be discussed in detail. The changes in voltage will be demonstrated before and after STATCOM. This will help reduce the negative impact and avoid equipment failure on a very large scale.